Optimization of wear and hardness of Al–Zn–Mg–Cu alloy fabricated from recycled beverage can using response surface methodology - Kazeem, Abubakar; Badarulzaman, Nur Azam; Wan Ali, Wan Fahmin Faiz (Springer, 2020)
A novel X7475 (Al–Zn–Mg–Cu) alloy was fabricated from recycled beverage cans (RBCs). Al was recovered from RBC. Zn and Mn were sourced from spent batteries, while Cu was sourced from copper wire. The weight percent (wt%) Zn was varied at 4, 4.5 and 5. Following the fabrication of rods, samples were taken through precipitation and artificial ageing at 475 °C and 145 °C respectively. The pin-on disc method within ASTM G99-17 was used for the wear test, while hardness post-mortem was done using ASTM E18 specifications. Wear mass loss (WML) and hardness were optimized using response surface methodology (RSM). The least WML of 0.017 g and maximum hardness of 142 HV were obtained from an alloy fabricated using 5 wt% Zn, when subjected to a load (L) of 30 N, speed (S) of 400 RPM and time (T) of 10 min. The MWL of 0.011 g and least hardness of 71 HV were observed in an alloy of 4 wt% Zn under a load of 20 N, with S, and T at 150 RPM and 6 min apiece. Formation of hardening precipitates like Al2CuMg, MgZn2 and CuAl2, were suggested to be responsible for the low WML and hardness observed in the alloys. The result confirmed the significant of the optimization model at a confident interval of 95% ( R2 = 0.9531). Additional experiment was suggested for correlating hardness with tensile strength.